Detachment mechanism and reduced evaporation of an evaporative NaCl salt crust - G. Licsandru; C. Noiriel; S. Geoffroy; A. Abou-Chakra; P. Duru; M. Prat (Scientific Reports, 2022)
Abstract Salt crusts forming at the surface of a porous medium are commonly observed in nature as well as on building materials and pieces of our cultural heritage where they represent a risk for the supporting substrate integrity. Previous research indicates that the salt crust can detach from the porous substrate and severely reduces the evaporation. However, the current understanding of the detachment mechanisms and the reduced evaporation is very limited. In the present experiment, we evidence dissolution–precipitation processes as key mechanisms in the detachment process. We also show that the crust remains wet and the observed reduced evaporation is explained by the formation of tiny pores in the nanometer range and the Kelvin effect. The resulting crust permeability is very low. Combined with previous results, this shows that the crust permeability is highly dependent on the crust formation conditions. More generally, salt structures in a water vapor concentration gradient are shown to be self-propelled systems capable to carry small objects such as, for instance, soil particles. Our study has significance for understanding the impact of salt crusts on evaporation and the associated important phenomena, such as soil salinization and porous material degradation inherent to salt crystallization.